فعالية تطبيق نظرية المارسات الثلى لاستراتيجية أدارة الوارد البشرية على أداء قطاع الواصلات في محافظة ظفار بسلطنة عمان - Mohammed Suhail Ahmed Al-Hadhri
Best practice theory of human resource management strategy is regarded as one of the main theories that can influence organizations performance, including the private sector. The best practice theory has identified the factors that influence performance such as job security, selection, teamwork, compensation, training, information sharing, and reduction of status differences. However, the impact of these factors on the performance in private sectors organization, particularly in sultanate of Oman has not explored through empirical study. Therefore, this study was conducted to examine the effect of previous factors on the performance to private sector of Dhofar Governorate in Sultanate of Oman. In addition this study was conducted to examine the impact role of organizational behavior as a mediator in the relationship between variables included in this study. To answer the previous objectives, the data of this study have been collected through questionnaire among (394) from various functional levels in private sector organizations. This study has found that the factors that influence performance were job security, selection, teamwork, compensation, training, information sharing, and reduction of status differences influence. This study also reveals that organizational behaviour has a positive effect on performance in private sector. Finally, this study provides empirical evidence about the role of organizational behaviour as a mediator in the relationship between the factors that included in best practice theory and performance.